2020
DOI: 10.1002/eji.201948323
|View full text |Cite
|
Sign up to set email alerts
|

Itch attenuates CD4 T‐cell proliferation in mice by limiting WBP2 protein stability

Abstract: To mount an antipathogen response, CD4 T cells must undergo rapid cell proliferation; however, poorly controlled expansion can result in diseases such as autoimmunity. One important regulator of T-cell activity is the E3 ubiquitin ligase Itch. Itch deficient patients suffer from extensive autoinflammation. Similarly, Itch deficient mice exhibit inflammation characterized by high numbers of activated CD4 T cells. While the role of Itch in limiting CD4 T-cell cytokine production has been extensively studied, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…In conclusion, we demonstrated that WBP2 drives TNBC migration and invasion under TNF‐α‐induced conditions, which mimic the tumor‐stimulatory microenvironment. Although previous studies hinted the possible involvement of WBP2 in inflammation, via its binding to ITCH [17,82], a negative regulator of TNF/NF‐κB signaling, this study shows for the first time a participatory role of WBP2 in tumor inflammatory signaling, particularly in TNF/NF‐κB signaling pathway. Moreover, its regulation on BTRC mRNA stability highlights an alternative mode of action of WBP2 as a posttranscriptional regulator, besides its widely reported functional role as a transcriptional coactivator.…”
Section: Discussioncontrasting
confidence: 52%
“…In conclusion, we demonstrated that WBP2 drives TNBC migration and invasion under TNF‐α‐induced conditions, which mimic the tumor‐stimulatory microenvironment. Although previous studies hinted the possible involvement of WBP2 in inflammation, via its binding to ITCH [17,82], a negative regulator of TNF/NF‐κB signaling, this study shows for the first time a participatory role of WBP2 in tumor inflammatory signaling, particularly in TNF/NF‐κB signaling pathway. Moreover, its regulation on BTRC mRNA stability highlights an alternative mode of action of WBP2 as a posttranscriptional regulator, besides its widely reported functional role as a transcriptional coactivator.…”
Section: Discussioncontrasting
confidence: 52%
“…GOplot algorithm was employed to visualize the gene ontology analysis results [ 92 ]. The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE [ 93 ] partner repository with the data set identifier PXD017699 and PXD019272 [ 94 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the endocrine system, WBP2 can be involved in insulin signaling and lipid metabolism (29,30) and may also be involved in thyroid differentiation in conjunction with Pax8 (16). More than that, WBP2 can also be promoted to degradation by itchy E3 ubiquitin-protein ligase (ITCH) to attenuate the proliferation of CD4 + T cells and hence participate in the inflammatory response (31). In addition, WBP2 can activate oocytes, and takes the same position as WW binding protein 2 N-terminal like (WBP2NL) in mouse sperm (32).…”
Section: Wbp2-associated Cancers and Diseasesmentioning
confidence: 99%